The Effect of Testosterone Administration and Digit Ratio (2D:4D) on Implicit Preference for Status Goods in Healthy Males - Wu, Yin; Zilioli, Samuele; Eisenegger, Christoph; Clark, Luke; Li, Hong (Frontiers in Behavioral Neuroscience, 2017)
Testosterone has been linked to social status seeking in humans. The present study investigated the effects of testosterone administration on implicit and explicit preferences for status goods in healthy male participants (n = 64), using a double-blind, placebo-controlled, between-subjects design. We also investigated the interactive effect between second-to-fourth digit ratio (2D:4D; i.e. a proximal index of prenatal testosterone) and testosterone treatment on status preferences. Results showed that testosterone has no discernable influence on self-reported willingness-to-pay (i.e. the explicit measure) or implicit attitudes towards status goods. Individuals with lower 2D:4D (i.e., more masculine) had more positive attitudes for high-status goods on an Implicit Association Task, and this association was abolished with testosterone administration. These data suggest interactive effects of acute testosterone administration and prenatal testosterone exposure on human social status seeking, and highlight the utility of implicit methods for measuring status-related behavior.